2006
DOI: 10.1159/000097308
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Prosody to the Perception of Foreign Accent

Abstract: The general goal of this study was to expand our understanding of what is meant by ‘foreign accent’. More specifically, it deals with the role of prosody (timing and melody), which has rarely been examined. New technologies, including diphone speech synthesis (experiment 1) and speech manipulation (experiment 2), are used to study the relative importance of prosody in what is perceived as a foreign accent. The methodology we propose, based on the prosody transplantation paradigm, can be applied to different la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(22 citation statements)
references
References 32 publications
1
19
0
2
Order By: Relevance
“…Research has demonstrated that listeners can be adept at identifying the native language of foreign-accented speech on the basis of prosody alone, such as when the content is masked (De Mareuil & Viery-Dimulescu, 2006;Munro, Derwing, & Burgess, 2010;Trofimovich & Baker, 2006;Vicenik & Sundara, 2013). In American English (AE), listeners typically segment speech at strong (inflected) syllables, whereas in languages such as French, which has many fewer examples of strong-weak syllabic contrasts, listeners identify word boundaries on the basis of other rhythmic cues (Cutler & Butterfield, 1992).…”
Section: Segmental and Prosodic Dimensions Of Foreign Accentmentioning
confidence: 99%
“…Research has demonstrated that listeners can be adept at identifying the native language of foreign-accented speech on the basis of prosody alone, such as when the content is masked (De Mareuil & Viery-Dimulescu, 2006;Munro, Derwing, & Burgess, 2010;Trofimovich & Baker, 2006;Vicenik & Sundara, 2013). In American English (AE), listeners typically segment speech at strong (inflected) syllables, whereas in languages such as French, which has many fewer examples of strong-weak syllabic contrasts, listeners identify word boundaries on the basis of other rhythmic cues (Cutler & Butterfield, 1992).…”
Section: Segmental and Prosodic Dimensions Of Foreign Accentmentioning
confidence: 99%
“…There are few studies, however, which have examined the influence of prosody on foreign accent rating. Relying on acoustic analyses, previous studies have reported that prosody is critical in the perception of accent (Anderson-Hsieh, Johnson, & Koehler, 1992; Boula de Mareüil, & Vieru-Dimulescu, 2006; Gilbert, 1984; Munro, 1995). Specifically, temporal variation, which is an index of prosodic modulation, is reported to be an important contributor to the perception of foreign accent (Tajima, Port, & Dalby, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The foreign accent can be defined as the quantitative difference between two phonological systems in which one is the native language (L1) and the other is the foreign language (L2; Boula de Mareüil & Vieru-Dimulescu, 2006).…”
Section: Introductionmentioning
confidence: 99%